Floaters : poems - Espada, Martín, 1957- (W. W. Norton, 2021)
"From the winner of the Ruth Lilly Poetry Prize come masterfully crafted narratives of protest, grief, and love. In this collection, Martín Espada bears witness to confrontation with anti-immigrant bigotry as a tenant lawyer years ago, and now sings the praises of Central American adolescents playing soccer in an internment camp founded on that same bigotry. He knows that times of hate also call for poems of love--even in the voice of a Galápagos tortoise. Whether celebrating the visions of fallen dreamers and poets or condemning the devastation of Hurricane Maria and official negligence in his father's Puerto Rico, Espada invokes ferocious, incandescent spirits"--